Visual Identity Design for Mas Joko, the Auto Trader Efforts to Increase Brand Awareness - Lukas Sugiyanto; Dhani Agustinus; Ivan Budi Rianto (SEAN Institute, 2026)
This research aims to redesign the Mas Joko Pedagang Oto logo and standardize its application through application media. The research method uses research and development with a descriptive approach. The design technique uses Designing Brand Identity while data collection is done by observation and interviews. The results of the redesign of